Serum Myoglobin Is Associated With Postoperative Acute Kidney Injury in Stanford Type A Aortic Dissection - Yang, Chen; Hou, Peng; Wang, Dongxu; Wang, Zhenguo; Duan, Weixun; Liu, Jincheng; Yu, Shiqiang; Fu, Feng; Jin, Zhenxiao (Frontiers in Medicine, 2022)
Background: The correlation between rhabdomyolysis and postoperative acute kidney injury has been reported in several surgical procedures. As a good predictor of rhabdomyolysis-related acute kidney injury, an elevated serum myoglobin level was often observed after total aortic arch replacement combined with frozen elephant trunk implantation. However, the correlation between serum myoglobin and acute kidney injury in such patients had not been established. Methods: Totally 398 stanford type A aortic dissection patients who underwent total aortic arch replacement combined with frozen elephant trunk implantation were enrolled in this retrospective study. The correlations between serum myoglobin and acute kidney injury as well as the 30-day mortality were assessed. Results: Overall, 268(67.3%) patients had acute kidney injury (KDIGO stage 1 or higher) and 75(18.8%) had severe acute kidney injury (KDIGO stage 2&3). Patients who developed acute kidney injury had higher level of perioperative serum myoglobin than patients without acute kidney injury. After adjusting for known acute kidney injury risk factors, logarithmically transformed preoperative serum myoglobin (OR=1.66 (95%CI, 1.32-2.08), P<0.001) and postoperative day 1 serum myoglobin (OR=3.25 (95%CI, 2.14-4.96), P<0.001) were associated with severe acute kidney injury. These correlation persisted after adjustment for decline in filtration (via change in serum creatinine (ΔCr) and biomarkers of cardiac and kidney injury, including N-terminal prohormone of brain natriuretic peptide, cardiac troponin I, creatine kinase-MB, serum creatinine and Cystatin C. Compared with the clinical model, sMb considerably improved the risk discrimination and reclassification for AKI. Conclusion: For stanford type A aortic dissection patients underwent total aortic arch replacement with frozen elephant trunk implantation, serum myoglobin can improve postoperative acute kidney injury risk classification. Rhabdomyolysis is an important supplement to the existing knowledge on the mechanism of acute kidney injury.